Importance of Multi-Stakeholder Needs Analysis to Develop LSP Module: - Debashismoy Dutta; Prabal Das Gupta (Crossings, 2015)
This paper reviews and reflects on the needs analysis conducted to develop a trade-specific Language for Specific Purposes (LSP) module for prospective migrant workers incorporating English-Bangla-Arabic in a tripartite collaboration with the International Labour Organization (ILO), Bureau of Manpower, Employment and Training (BMET) and BRAC Institute of Languages (BIL). This paper explores the multifaceted nature of this needs analysis by asking some questions – what module, for whom, to serve what purpose, at what cost, under whose supervision, by whom and under what logistic setting.The analysis was carried out by observing classes and interviewing prospective migrant workers at Technical Training Centres (TTCs), interviewing the TTC instructors, conducting focus group discussions (FGD) with returnee migrant workers, sharing ideas with ILO personnel and advocacy groups such as BRAC Migration Program (MP). This process helped the researchers identify the target groups’ fragmented knowledge about target discourse situations which was somewhat compensated by the experiences of returnees. The expertise of the instructors helped to categorize the typical strengths and weaknesses of target groups and under continuous efforts of ILO to enforce international best practices for a decent working environment for migrant workers. Taking into consideration the multiplicity of issues and various inputs from the stakeholders, this paper underpins the importance of a multi-stakeholder needs analysis for better comprehension of the target discourse situation and appropriate delivery of services with some suggestions for future LSP modules.